1943
DOI: 10.1007/bf02637339
|View full text |Cite
|
Sign up to set email alerts
|

The viability, chemical composition and internal microflora of frost damaged soybeans

Abstract: Summary Seven composite samples of Minnesota grown soybeans and seven individual lots of Illinois soybeans of the 1942 crop containing varying percentages of immature and frost‐damaged seeds were subjected various analyses. Increased damaged‐seed content was accompanied by a marked decrease in viability and by increases in phosphate acidity, amino‐acid acidity, nonprotein nitrogen, reducing sugars, and in the internal aerobic microfloral content of the seeds. Proximate composition of the samples within each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1961
1961
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…Oil content Prior to storage, freeze-damaged samples of both the Williams and Clark 63 varieties, had slightly lower oil percentages than control samples of the same variety. This would confirm data from Milner et al (1943) which showed that as the number of freeze-damaged seeds in a sample increases, the oil percentage decreases. However, none of the samples showed a statistically significant change in oil percentage during storage.…”
Section: Protein Contentsupporting
confidence: 87%
See 2 more Smart Citations
“…Oil content Prior to storage, freeze-damaged samples of both the Williams and Clark 63 varieties, had slightly lower oil percentages than control samples of the same variety. This would confirm data from Milner et al (1943) which showed that as the number of freeze-damaged seeds in a sample increases, the oil percentage decreases. However, none of the samples showed a statistically significant change in oil percentage during storage.…”
Section: Protein Contentsupporting
confidence: 87%
“…Most of the reported occurrences of freeze damage are in the northern soybean producing states. Milner et al (1943) (1980) to the extent that in some samples 55% of the beans were green and shriveled. Sanders (1946) reported that freeze damage increased the normal chlorophyll content of the crude oil a hundred fold.…”
Section: Introduction Althoughmentioning
confidence: 99%
See 1 more Smart Citation
“…Melvin et al (1953) also found that as the proportion of damaged frozen bean seeds increased, so did the free fatty acid content of the crude lipid. Milner et al (1943) reported that as the percentage of damaged seeds in a freezestored sample increased, there was a corresponding increase in non-protein nitrogen and reducing sugars. These increases were suggested to be the result of stimulated enzyme activity in response to the freezing process.…”
Section: Resultsmentioning
confidence: 99%
“…1D-F (Mills and Sinha 1980 (Mills, Van Caeseele and Daun, in prep . ) , destroyed the integrity of immature cells permitting increased leakage of electrolytes and also may have increased seed enzymatic activity (Milner et al 1943). …”
mentioning
confidence: 99%